Peningkatan Pengetahuan Siswa SD 09 Banda Sakti Melalui Penyuluhan tentang Bencana Tsunami - Wheny Utariningsih; Vera Novalia; Rizka Sofia; T Saifullah (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2022)
SD 9 Banda Sakti is located in Lhokseumawe City which based on a disaster risk assessment has medium to high risk of a tsunami disaster. The initial discussion of the service team with SD 09 Banda Sakti concluded that SD 09 Banda Sakti had never received counseling related to disasters, especially the tsunami disaster. Whereas SD 09 Banda Sakti is one of the schools located directly opposite the beach. Therefore, it is necessary to carry out tsunami disaster counseling at SD 09 Banda Sakti. In addition to counseling about the tsunami disaster, SD 09 Banda Sakti also needs to get counseling about little doctors so that students are able to become agents of change to behave in a clean and healthy life and respond to disasters. This counseling is very needed to be a provision for students who are in high risk areas for tsunami disaster. The method used in this activity, which was attended by 85 students was lecture and singing. Based on the pre-test and post-test, this outreach activity can increase students' knowledge about the tsunami disaster by 40%.